Investigation of electrically active defects in InGaAs quantum wire intermediate-band solar cells using deep-level transient spectroscopy technique. (20th December 2016) - Al Saqri, Noor alhuda; Felix, Jorlandio F; Aziz, Mohsin; Kunets, Vasyl P; Jameel, Dler; Taylor, David; Henini, Mohamed; Abd El-sadek, Mahmmoud S; Furrow, Colin; Ware, Morgan E; Benamara, Mourad; Mortazavi, Mansour; et al.
Abstract: InGaAs quantum wire (QWr) intermediate-band solar cell–based nanostructures grown by molecular beam epitaxy are studied. The electrical and interface properties of these solar cell devices, as determined by current–voltage (I–V) and capacitance–voltage (C-V) techniques, were found to change with temperature over a wide range of 20–340 K. The electron and hole traps present in these devices have been investigated using deep-level transient spectroscopy (DLTS). The DLTS results showed that the traps detected in the QWr-doped devices are directly or indirectly related to the insertion of the Si δ -layer used to dope the wires. In addition, in the QWr-doped devices, the decrease of the solar conversion efficiencies at low temperatures and the associated decrease of the integrated external quantum efficiency through InGaAs could be attributed to detected traps E1QWR_D, E2QWR_D, and E3QWR_D with activation energies of 0.0037, 0.0053, and 0.041 eV, respectively.